2021
DOI: 10.1111/vec.13109
|View full text |Cite
|
Sign up to set email alerts
|

Red cell distribution width is a predictor of all‐cause mortality in hospitalized dogs

Abstract: Objective: To determine whether RBC distribution width (RDW) is associated with an increased odds of mortality in hospitalized dogs and cats.Design: Retrospective, single-center study; data collected from 2007 to 2017. Setting: University teaching hospital.Animals: Six thousand six hundred and sixty-one animals (5183 dogs and 1478 cats). Interventions: None.Measurements and Main Results: Medical records were identified from animals presented to the emergency service and admitted to the ICU with a CBC and serum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 38 publications
2
12
0
Order By: Relevance
“…Furthermore, no correlation was found between RDW and RDW/Ca, and RBC, Hb and Hct, with the only exception of weak negative correlation between RDW and Hct. The association between RDW and regenerative anemia has been demonstrated in previous studies on dogs with various systemic and cardiovascular disorders [22][23][24][25][26][27][28][29]. Our findings suggest that the increased RDW and RDW/Ca in non-survivor dogs were not correlated to anemia and confirmed that anemia was not associated with a negative prognosis in dogs with AP [1][2][3]7].…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Furthermore, no correlation was found between RDW and RDW/Ca, and RBC, Hb and Hct, with the only exception of weak negative correlation between RDW and Hct. The association between RDW and regenerative anemia has been demonstrated in previous studies on dogs with various systemic and cardiovascular disorders [22][23][24][25][26][27][28][29]. Our findings suggest that the increased RDW and RDW/Ca in non-survivor dogs were not correlated to anemia and confirmed that anemia was not associated with a negative prognosis in dogs with AP [1][2][3]7].…”
Section: Discussionsupporting
confidence: 83%
“…Similar results were obtained when RDW/Ca > 1.4 was used in the multivariable model instead of RDW > 12.7% (data not shown). Two recent studies reported the relationship between increased RDW and all-cause mortality in dogs with myxomatous mitral valve disease and those hospitalized for different disorders [ 25 , 29 ]. Conversely, RDW did not predict all-cause mortality in dogs with trauma and those admitted to the intensive care unit of a referral veterinary hospital for miscellaneous disorders [ 26 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent articles have reported the results of RDW evaluation in animals with different severe diseases [ 19 , 20 , 21 ]. Ludwik et al [ 20 ] assessed the relationship between RDW and mortality using logistic regression modeling in 6661 hospitalized animals, including 5183 dogs and 1478 cats.…”
Section: Red Blood Cell Distribution Width and Critical Ill Dogs/hosp...mentioning
confidence: 99%
“…Similar to the developments in human medicine, some studies investigating the use of RDW as a novel marker have also been recently published in various animal clinical settings. In particular, these studies have been conducted in small animals with cardiovascular disease [ 10 , 11 , 12 , 13 , 14 , 15 ] and other various disorders [ 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. Therefore, the aim of this review is to provide the most relevant information on RDW evaluation in the dog.…”
Section: Introductionmentioning
confidence: 99%